2008
DOI: 10.1590/s1806-83242008000200009
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole-containing gel for the treatment of periodontitis: an in vivo evaluation

Abstract: The aim of this investigation was to monitor metronidazole concentrations in the gingival crevicular fluid (GCF) collected from periodontal pockets of dogs after treatment with an experimental 15% metronidazole gel. Five dogs had periodontitis induced by cotton ligatures placed subgingivally and maintained for a 30-day period. After the induction period, only pockets with 4 mm or deeper received the gel. Each pocket was filled up to the gingival margin by means of a syringe with a blunt-end needle. GCF was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
(23 reference statements)
1
24
0
1
Order By: Relevance
“…For treating periodontitis, a number of resorbable drug delivery systems were developed during recent decades, such as drug loaded hydroxypropyl cellulose films [8], or drug carrying gels such as Elyzol® (Dumex GmbH, Bad Vilbel, Germany) dental gel, based on melted glycerol mono-oleate [9,10]. However, for these systems, the periodontal milieu often poses the major problem that the required period of drug exposure (7-10 days) cannot be achieved [11].…”
Section: Introductionmentioning
confidence: 99%
“…For treating periodontitis, a number of resorbable drug delivery systems were developed during recent decades, such as drug loaded hydroxypropyl cellulose films [8], or drug carrying gels such as Elyzol® (Dumex GmbH, Bad Vilbel, Germany) dental gel, based on melted glycerol mono-oleate [9,10]. However, for these systems, the periodontal milieu often poses the major problem that the required period of drug exposure (7-10 days) cannot be achieved [11].…”
Section: Introductionmentioning
confidence: 99%
“…The gel was applied twice a day for 7 days. This procedure was based on a procedure proposed by Sato et al 16 The exceess gel on the gingival sulcus then was cleaned with a cotton pellet.…”
Section: Methodsmentioning
confidence: 99%
“…The local delivery of metronidazole gel is advantageous because of the ability of releasing antimicrobial agents in concentrations high enough to affect pathogens, even in subgingival biofilms. [38] Stellini et al verified efficacy of metronidazole dental gel 25%, used as a topical antibiotic for the treatment of peri-implantitis and found that peri-implant diseases can be positively resolved with 60-70% decrease of Gram-negative and 40-50% increase in Gram-positive organisms and a good peri-implant soft tissue recovery. [39,40] …”
Section: Metronidazolementioning
confidence: 99%